Combining cover crops and low nitrogen fertilization improves soil supporting functions - Restovich, Silvina Beatriz; Andriulo, Adrian Enrique; Armas- Herrera, Cecilia María; Beribe, Maria Jose; Portela, Silvina Isabel (2019)
Background and aims: Cover crops may restore soil functions lost with single summer crop sequences enhancing soil organic carbon and nitrogen (SOC and SON) stocks. We investigated the effect of cover crops and low nitrogen (N) fertilization on SOC and SON and soil structure (pore size distribution and aggregate stability), and connected changes with cover crop-related variables. Methods: We used a six-year experiment with different winter cover crops in a maize-soybean rotation under no tillage with or without N fertilization of maize (32 kg ha−1). Results: Most cover crops increased SOC (0.36 ± 0.23 Mg ha−1 yr.−1) and vetch also increased SON in the absence of N fertilization. With cover crops, N storage shifted from inorganic to more stable organic forms (SON and cover crop biomass). Cover crops except forage radish increased soil porosity favoring 300–60 μm macropores (0–10 cm depth). Soil aggregation at 0–5 cm depth was more stable with than without cover crops (43 and 25%, respectively). The effect of glomalin as aggregation agent was observed in the absence of N fertilization. Conclusions: Increased N retention and input (in the case of vetch), combined with C input from cover crops, increased organic reserves and improved soil structure, enabling N fertilization reduction.